Aktualisasi Konsep Keluarga Sakinah Mawadah Warahmah pada Jamaah Kompolan Muslimat Desa Pakondang - Kulsum, Ummi (At-Turost : Journal of Islamic Studies, 2023)
Abstract: The form of a sakinah mawadah warahmah family is an actualization carried out by the Muslim congregation of Pakondang Village in fostering an ideal household. In addition, there are other factors that also contribute to the achievement of these goals. This research uses a type of qualitative research, namely research that seeks to organize data in units in the form of all observable events, activities, and messages. Using a purposive sampling technique is a technique for determining informants with certain considerations. such as the informant is a person who is considered to know about what is expected by the researcher. the object of this research is 10 respondents who represent 50 respondents of Muslim congregation in Pakondang village. The next step is to classify the data that has been coded according to the themes of each cognate and the final step is to interpret the opinions, so that patterns, categories and general assumptions about the research topic will be obtained.While the results of this study are: First, the actualization of a sakinah mawadah warahmah family is a family in which the values ​​of faith and obedience to Allah SWT are instilled, namely carrying out all His commands and leaving His prohibitions. Second, establish good communication, so that misunderstandings do not occur which cause discomfort and disharmony in the family. and Third, there is motivation between family members, husband and wife so that they always support each other, especially in terms of the family economy. Keywords: Actualization, Family Sakinah mawaddah Warahmah, members of the Muslim Compolan